CREDIT RISK MANAGEMENT AT BANK BENGKULU MAIN BRANCH DURING COVID-19 PANDEMIC - Martini, Tri; Husaini, Husaini; Sari, Novita (JURNAL FAIRNESS, 2020)
This research purpose is to describe credit risk management at Bank Bengkulu during covid-19 pandemic. This research is a descriptive study that focuses on the phenomenon of activity, namely credit risk management activities done by credit analysts, branch vice leaders and branch leaders. Data collection is done through observations, interviews and documentation that are intended to test each other on the information obtained. This research concluded that credit risk management conducted by Bank Bengkulu main branch is credit risk identification, credit risk measurement and assessment, credit risk control and credit risk monitoring. This research found in the identification stage, credit risk measurement and assessment is done by credit analysts manually or subjectively by making credit analysis reports. During the Covid-19 pandemic, business sectors directly affected such as tourism, hospitality, transportation and service sectors were temporarily suspended for credit disbursement.